Hospital door handle design and their contamination with bacteria: a real life observational study. Are we pulling against closed doors? - Hedieh Wojgani; Catherine Kehsa; Elaine Cloutman-Green; Colin Gray; Vanya Gant; Nigel Klein (PLoS ONE)
Objective To determine whether microbial contamination of door handles in two busy intensive care units and one high dependency unit was related to their design, location, and usage. Design Observational study of the number of viable bacteria on existing door handles of different design at defined entry/exit points with simultaneous data collection of who used these doors and how often. Setting Two busy specialised intensive care units and one high dependency unit in a tertiary referral NHS neurological hospital. Main outcome measures Surface bacterial density on door handles with reference to design, location, and intensity of use. Results We found a significant correlation between the frequency of movements through a door and the degree to which it was contaminated (p=<0.01). We further found that the door's location, design and mode of use all influenced contamination. When compared to push plate designs, pull handles revealed on average a five fold higher level of contamination; lever handles, however, displayed the highest levels of bacterial contamination when adjusted for frequency of use. We also observed differences in contamination levels at doors between clinical areas, particularly between the operating theatres and one of the ICUs. Conclusions Door handles in busy, "real life" high acuity clinical environments were variably contaminated with bacteria, and the number of bacteria found related to design, location, mode and frequency of operation. Largely ignored issues of handle and environmental design can support or undermine strategies designed to limit avoidable pathogen transmission, especially in locations designed to define "thresholds" and impose physical barriers to pathogen transmission between clinical areas. Developing a multidisciplinary approach beyond traditional boundaries for purposes of infection control may release hitherto unappreciated options and beneficial outcomes for the control of at least some hospital acquired infections.